2022
DOI: 10.3390/ijerph19020972
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients with Prostate Cancer Benefit from Exercise Interventions? A Systematic Review and Meta-Analysis

Abstract: Men diagnosed and treated for prostate cancer experience severe adverse effects on quality of life (QoL) and metabolic health, some of which may be preventable or reversible with exercise, the benefits of which healthcare providers and patients increasingly acknowledge, though existing evidence on its effects varies in significance and magnitude. We aimed to review the effect of exercise on QoL and metabolic health in a broad prostate cancer population. A systematic search was conducted in nine databases and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…A recent meta-analysis of 18 randomized controlled trials, including 1477 patients with prostate cancer undergoing androgen deprivation therapy, reported that supervised exercise therapy has a moderately positive effect on disease-specific quality of life compared to no exercise therapy ( 44 ). On the other hand, another recent meta-analysis comprising 17 randomized controlled trials, involving 1361 patients with prostate cancer who had received cancer treatment, concluded that exercise had a small effect on cancer-specific QoL, and no differences were observed between exercise modalities ( 45 ). In addition, like a previous report ( 33 ), we did not observe changes in health-related QoL in patients with prostate cancer that participated in WF practice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 18 randomized controlled trials, including 1477 patients with prostate cancer undergoing androgen deprivation therapy, reported that supervised exercise therapy has a moderately positive effect on disease-specific quality of life compared to no exercise therapy ( 44 ). On the other hand, another recent meta-analysis comprising 17 randomized controlled trials, involving 1361 patients with prostate cancer who had received cancer treatment, concluded that exercise had a small effect on cancer-specific QoL, and no differences were observed between exercise modalities ( 45 ). In addition, like a previous report ( 33 ), we did not observe changes in health-related QoL in patients with prostate cancer that participated in WF practice.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT), the mainstay of therapy for metastatic disease, has been shown to significantly increase overall survival ( Supplementary material [S3]) [3] ; yet, it is also known to cause metabolic complications including cardiovascular disease, obesity, and diabetes ( Supplementary material [S4]) [4] . ADT is more likely to cause fatigue than surgery or radiation alone even when used to treat localised prostate cancer ( Supplementary material [S5,6]) [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…These adversely impact a man’s ability to work and carry out daily activities, thereby negatively affecting his personal relationships and overall quality of life ( Supplementary material [S10]) [12] . As men with prostate cancer are surviving longer, side effects of treatment, such as cancer-related fatigue, are becoming increasingly important to understand and manage, as these may disrupt the lives of prostate cancer patients more than the cancer itself ( Supplementary material [S10]) [5] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current level of favourable clinical outcomes, physical activity (PA) has been considered to be one of the most beneficial interventions in preventing or relieving fatigue and has been recommended in the clinical guidelines (Okely et al, 2021 ; Thong et al, 2020 ). Several systematic reviews and meta‐analyses concluded the effects of PA intervention on CRF (Andersen et al, 2022 ; Liu et al, 2021 ; Medeiros Torres et al, 2022 ; Toohey et al, 2022 ; Van Vulpen et al, 2020 ), and most of these studies showed positive outcomes (Liu et al, 2021 ; Medeiros Torres et al, 2022 ; Toohey et al, 2022 ; Van Vulpen et al, 2020 ). However, there is significant heterogeneity due to these studies mainly focusing on survivors diagnosed with breast cancer or prostate cancer (Andersen et al, 2022 ; Liu et al, 2021 ; Medeiros Torres et al, 2022 ; Toohey et al, 2022 ; Van Vulpen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta‐analyses concluded the effects of PA intervention on CRF (Andersen et al, 2022 ; Liu et al, 2021 ; Medeiros Torres et al, 2022 ; Toohey et al, 2022 ; Van Vulpen et al, 2020 ), and most of these studies showed positive outcomes (Liu et al, 2021 ; Medeiros Torres et al, 2022 ; Toohey et al, 2022 ; Van Vulpen et al, 2020 ). However, there is significant heterogeneity due to these studies mainly focusing on survivors diagnosed with breast cancer or prostate cancer (Andersen et al, 2022 ; Liu et al, 2021 ; Medeiros Torres et al, 2022 ; Toohey et al, 2022 ; Van Vulpen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%